Confocal Microscopy of Reovirus Transport in Living Dorsal Root Ganglion Neurons - Pavithra Aravamudhan; Krishnan Raghunathan; Terence Dermody (Bio-Protocol, 2020)
Neurotropic reoviruses repurpose host machinery to traffic over long distances in neuronal processes and access distal replication sites. Understanding mechanisms of neuronal transmission is facilitated by using simplified in vitro primary neuronal culture models. Advances in the design of compartmentalized microfluidic devices lend robustness to neuronal culture models by enabling compartmentalization and manipulation of distinct neuronal processes. Here, we describe a streamlined methodology to culture sensory neurons dissociated from dorsal root ganglia of embryonic rats in microfluidic devices. We further describe protocols to exogenously label reovirus and image, track, and analyze transport of single reovirus particles in living neurons. These techniques can be adapted to study directed axonal transport of other neurotropic viruses and neuronal factors involved in signaling and pathology.